2003
DOI: 10.2140/gtm.2002.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Skein module deformations of elementary moves on links

Abstract: This paper is based on my talks ("Skein modules with a cubic skein relation: properties and speculations" and "Symplectic structure on colorings, Lagrangian tangles and its applications") given in Kyoto (RIMS), September 11 and September 18 respectively, 2001. The first three sections closely follow the talks: starting from elementary moves on links and ending on applications to unknotting number motivated by a skein module deformation of a 3-move. The theory of skein modules is outlined in the problem section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Twist moves have long been studied in knot theory. For a recent survey, see Przytycki [70]. Here we give a few examples from the literature with translations into our setting.…”
Section: Twist Movesmentioning
confidence: 99%
“…Twist moves have long been studied in knot theory. For a recent survey, see Przytycki [70]. Here we give a few examples from the literature with translations into our setting.…”
Section: Twist Movesmentioning
confidence: 99%
“…Of particular interest in knot theory are 4-moves. One of the reasons is the following old conjecture [Kir,Pr1,Pr2].…”
Section: The Lower Bound For the 4-move Distance Between Linksmentioning
confidence: 99%
“…Not every link is 4-move equivalent to a trivial link, in particular, the linking matrix modulo 2 is preserved by 4-moves. Furthermore, Nakanishi demonstrated that the Borromean rings cannot be reduced to the trivial link of three components [Nak,Pr2]. Kawauchi expressed the question for links as follows:…”
Section: The Lower Bound For the 4-move Distance Between Linksmentioning
confidence: 99%
See 1 more Smart Citation
“…For string links, it is equivalent to a construction of Le Dimet [5]. We refer to [6,7] and references therein for related work on invariants of tangles.…”
mentioning
confidence: 99%